‘Don’t let anyone bring me down again’: applying ‘possible selves’ to understanding persistence of mature-age first-in-family students. - Delahunty, Janine; O'Shea, Sarah (Taylor & Francis, 2020)
This article applies the framework of possible selves to the motivation and persistence behaviours of one group of university students. We draw on possible selves to consider how particular goal-focused actions and life experiences may significantly shape movements towards imagined futures. Utilising a narrative approach from longitudinal data, this article considers the ways in which possible selves were articulated by five first-in-family students, all of whom were mature-aged women returning to formal learning. A series of vignettes enabled us to explore how students themselves conceived of this movement into university, and how hoped-for selves were considered and enacted (or not). The ways in which societal expectations and expected life trajectories impact (re)conceptualisation of ‘selves’ are discussed, particularly when individuals choose an unexpected or non-normative life course.